Softly blows the bugle - Drexler, Jan (Drexler, Jan. Amish of Weaver's Creek, 2020)
"After a disastrous marriage, a young Amish widow determines to remain unmarried. Will a wounded war veteran convince her to risk giving her heart away once more?"--